2000
DOI: 10.1093/jn/130.8.2105s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocoa Extracts on Endothelium-Dependent Relaxation

Abstract: The aim of this study was to examine the effects of procyanidins derived from cocoa on vascular smooth muscle. Two hypotheses were tested: 1) extracts of cocoa, which are rich in procyanidins, cause endothelium-dependent relaxation (EDR), and 2) extracts of cocoa activate endothelial nitric oxide synthase (NOS). The experiments were carried out on aortic rings obtained from New Zealand White rabbits. The polymeric procyanidins (tetramer through decamer of catechin) caused an EDR. In addition, the Ca(2+)-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
153
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(166 citation statements)
references
References 12 publications
7
153
2
2
Order By: Relevance
“…Experiments were carried out by using isolated rabbit (New Zealand Whites) aortic rings as detailed in ref. 39. We controlled for artifacts that might be caused by hydrogen peroxide, a product of flavanol decomposition in buffers and media (40), by adding catalase (400 units͞ml) into the tissue bath.…”
Section: Flavanol-rich Cocoa Drinks Under Nos Inhibitionmentioning
confidence: 99%
“…Experiments were carried out by using isolated rabbit (New Zealand Whites) aortic rings as detailed in ref. 39. We controlled for artifacts that might be caused by hydrogen peroxide, a product of flavanol decomposition in buffers and media (40), by adding catalase (400 units͞ml) into the tissue bath.…”
Section: Flavanol-rich Cocoa Drinks Under Nos Inhibitionmentioning
confidence: 99%
“…These beneficial effects have been linked to flavanols, a sub-group of flavonoids -the polyphenolic family of antioxidant chemicals, which are found in abundance in various foods (Heiss et al 2005), including, but not limited to red wine, black tea, apples, onions and cocoa (Campia & Panza 2008). The benefits of flavanol consumption are purported to be due to increased nitric oxide (NO) synthase activity and therefore an increased supply of bio-active NO (Fisher et al 2003;Karim et al 2000), with numerous studies showing that both acute (Duffy et al 2001;Engler et al 2004;Heiss et al 2003;Leikert et al 2002) and chronic flavanol supplementation can improve endothelium dependent vasodilation (Fisher et al 2003;Karim et al 2000). Interest in flavanols spread when initial beliefs that the acidic environment of the stomach degraded flavanol oligomers were disproven (Kwik-Uribe & Bektash 2008;Rios et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…EC and CPCs have been shown to possess antiobesity and anti-diabetic properties [24][25][26] . Emerging data suggest that these bioactivities may be highly correlated to flavanol DP [27][28][29] . Recently, Yamashita et al 30 demonstrated that a tetrameric cocoa flavanol significantly improved insulin secretion in mice compared to monomeric, dimeric, and trimeric flavanols (EC, PC B 2 , and PC C 1 , respectively) 30 .…”
mentioning
confidence: 99%